2012
DOI: 10.1371/journal.pone.0029984
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Battling Starvation Stress: Low Levels of Ethanol Prolong Lifespan in L1 Larvae

Abstract: The nematode Caenorhabditis elegans arrests development at the first larval stage if food is not present upon hatching. Larvae in this stage provide an excellent model for studying stress responses during development. We found that supplementing starved larvae with ethanol markedly extends their lifespan within this L1 diapause. The effects of ethanol-induced lifespan extension can be observed when the ethanol is added to the medium at any time between 0 and 10 days after hatching. The lowest ethanol concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…The critical difference between the two buffers is ethanol: cholesterol dissolved in ethanol is added to S-basal, resulting in a final concentration of 0.1% (20 mM) ethanol. As little as 1 mM ethanol extends starvation survival to a similar degree, as do n-propanol and n-butanol but not methanol or isopropanol (Castro et al 2012). Clarke and colleagues showed that pharyngeal pumping is necessary for ethanol to extend survival and that it is used as a carbon source to synthesize fatty acids and amino acids (Castro et al 2012).…”
Section: Starvation Survival and Stress Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The critical difference between the two buffers is ethanol: cholesterol dissolved in ethanol is added to S-basal, resulting in a final concentration of 0.1% (20 mM) ethanol. As little as 1 mM ethanol extends starvation survival to a similar degree, as do n-propanol and n-butanol but not methanol or isopropanol (Castro et al 2012). Clarke and colleagues showed that pharyngeal pumping is necessary for ethanol to extend survival and that it is used as a carbon source to synthesize fatty acids and amino acids (Castro et al 2012).…”
Section: Starvation Survival and Stress Resistancementioning
confidence: 99%
“…As little as 1 mM ethanol extends starvation survival to a similar degree, as do n-propanol and n-butanol but not methanol or isopropanol (Castro et al 2012). Clarke and colleagues showed that pharyngeal pumping is necessary for ethanol to extend survival and that it is used as a carbon source to synthesize fatty acids and amino acids (Castro et al 2012). In this sense the larvae are not truly starved, but the carbon source alone is not sufficient to initiate larval development.…”
Section: Starvation Survival and Stress Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…3), with a speed of *0.02 mm/ s, a frequency of *10 reversals in 2 min, and a rate of *30 body bends in 30 s on Day 2. Since earlier-stage nematodes may have a more sensitive response to stress (Castro et al, 2012), we then investigated the response of larval nematodes to hypergravity and microgravity. After 6 h of treatment from L1 and L4 stages ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By carrying out the starvation in S complete medium as opposed to M9, the hatching nematodes are provided with a carbon source (ethanol), so that larvae do not develop but are not completely starved. 27,28 It has also been shown that arrested L1's are primed for rapid response to food and normal L1 growth rate is achieved within 3 hr after food becomes available. 29 However, it the possibility that the starvation step may alter the metabolism of C. elegans cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%